Peran Agama dalam Membangun Solidaritas Sosial di Masyarakat - Dara Amanda; Najwa Aulia; Shakila Sasta Firna; Shinta Uzana; Alfatihah Zahira (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Religion serves as a social institution with a significant influence on shaping community life, including the formation of social solidarity. This study aims to analyze how religious values contribute to creating social bonds, strengthening interpersonal relationships, and minimizing the potential for conflict within a pluralistic society. The research employs a qualitative method with a descriptive-analytical approach through library research, examining various relevant literature such as books, scientific journals, and official documents. The results indicate that religion functions as a source of moral values that foster a sense of care, togetherness, and mutual assistance among community members. Furthermore, religious institutions serve as platforms for social interaction that strengthen solidarity networks, both within small communities and broader society. Nevertheless, the potential for disintegration may arise if religious identity is exclusively opposed without regard for the value of tolerance. This study concludes that strengthening an inclusive and moderate understanding of religion is essential to optimizing the role of religion as a unifying force for social solidarity amid societal diversity.